Combating Phoenix Activity in Bangladesh: Insights from Australian Recent Reforms - Sheikh Solaiman (Sriwijaya Law Review, 2025)
Many businesspeople employ deceptive tactics to generate profit. Among the worst offenders are those engaged in illegal phoenixing—a deliberate scheme to evade creditors by transferring company assets be-fore the company is liquidated. The absence of robust legal safeguards against this unethical and economically harmful practice exacerbates creditors’ losses, often impacting small depositors. It is, therefore, the state’s responsibility to close legal loopholes and strengthen laws to curb phoenixing by unscrupulous corporate directors. Recognising this, Aus-tralia reinforced its corporate legal framework in 2020 by amending its corporations’ legislation to combat illegal phoenixing. The reform im-poses statutory duties on corporate officers, including directors, to pre-vent creditor-defeating dispositions and holds individuals personally liable—both criminally and civilly—for engaging in, procuring, facilitat-ing, or encouraging such asset transfers. In contrast, Bangladesh lacks specific legal prohibitions against phoenixing, despite facing a more se-vere problem than Australia. Instead of tackling corporate misconduct, regulatory efforts have primarily focused on disciplining lenders in loan approvals, leaving delinquent borrowers or indebted companies un-checked. This article primarily examines Australia’s recent anti-phoenixing reforms and proposes legal overhauls for Bangladesh to ad-dress this persistent issue. The recommendations aim to prevent fraudu-lent asset transfers, safeguard financial institutions, and hold accounta-ble culpable corporate directors and officers. The findings may also benefit other jurisdictions confronting similar challenges.